HUBUNGAN BULLYING DENGAN KEPERCAYAAN DIRI PADA REMAJA DI SMP NEGERI 10 MANADO (JURNAL KEPERAWATAN, 2018)
Abstract : Bullying is phenomena which is commently happened to teenagers especially in schools. It can be in the form of physical, verbal, and relational bullying. A teenage who have is a victim bullying can have impact on the shaping of his/her self confidence. The purpose of this research is to find out the relationship between bullying and their own self confidence in teenagers at 10 Junior High School Manado. The method of this research was descriptive analitic design by using cross sectional approach. As the sample of the research, there were have 54 participants of the students of 10 Junior High School by using total sampling technic. The instrument use was questionnaire. The research results tested by chi square statistics, is the value (p value = 0,000 < Î± = 0,05). The conclusion is there are relationships between bullying with their self confidence in teenagers at 10 Junior High School Manado. The research recommands, the teenagers to increase self confidence by trusting their own self, and to do counseling about bullying and how to cope with it.Keywords : Bullying, Self-confidence, TeenagersAbstrak : Bullying merupakan fenomena yang marak terjadi di kalangan remaja khususnya di lingkungan sekolah. Bullying yang diterima ini bisa secara fisik, verbal, dan relasional. Remaja yang mendapatkan perilaku bullying dari temannya dapat memengaruhi kepercayaan dirinya. Tujuan penelitian ini untuk mengetahui hubungan bullying dengan kepercayaan diri pada remaja di SMP Negeri 10 Mando. Metode penelitian ini menggunakan desain deskriptif analitik dengan pendekatan cross sectional. Sampel dalam penelitian ini berjumlah 54 responden siswa SMP Negeri 10 Manado dengan menggunakan teknik total sampling. Instrumen yang digunakan adalah kuesioner. Hasil penelitian dengan menggunakan uji statistik chi square diperoleh nilai (p value = 0,000 < 0,05). Kesimpulan ialah ada hubungan antara bullying dengan kepercayaan diri pada remaja di SMP Negeri 10 Manado. Saran bagi remaja agar dapat meningkatkan kepercayaan diri dengan yakin pada diri sendiri, serta diadakan penyuluhan tentang bullying dan penanggulangannya.Kata Kunci : Bullying, Kepercayaan Diri, Remaja